Hubungan Keterampilan Servis Atas dengan Ketepatan Servis Atas Peserta Ekstrakulikuler Bola Voli SMA Negeri 6 Kota Jambi - Puspita, Rina; Ilham; Setiawan, Iwan Budi (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aims to analyze the relationship between overhead service skills and overhead service accuracy in volleyball extracurricular participants at SMA Negeri 6 Jambi City. The research method uses a quantitative approach with a correlational design. The research sample consisted of 16 volleyball extracurricular participants selected using total sampling technique. The research instruments used observation sheets for overhead service skills and the AAHPER overhead service accuracy test. Data analysis used product moment correlation test. The results showed that the overhead service skills of extracurricular participants had a very good category of 7 people (43%), good category 3 people (19%), fair category 3 people (19%), and poor category 3 people (19%). Overhead service accuracy showed very accurate category 3 people (19%), accurate 6 people (37%), less accurate 6 people (37%), and inaccurate 1 person (7%). The correlation test resulted in rcount = 0.979 > rtable = 0.497 with a significance level of 0.05, indicating a very high and significant relationship between overhead service skills and overhead service accuracy.